Effect of Motivation, Organizational Culture and Commitment on Employees’ Performance: Department of Education and Culture of Papua - Farawowan, Fauziah F.; -, Mugiati (Information Management and Business Review, 2016)
The purposes of this study were: 1). To examine and analyze the influence of Motivation, Organizational Culture and Employee Commitment to Employee Performance in the Office of Education and Culture of the province of Papua, and 2) to examine and analyze the factors that most dominant influence on Employee Performance Office of Education and Culture of the Province of Papua. Data collection methods used were observation, interviews and questionnaires. Data were analyzed descriptively and quantitatively using Multiple Linear Regression Analysis. The sampling technique using the technique of "Sample Saturated" The results showed that: Partial factor in motivation (X1), Cultural Organization (X2), and Employee Commitment (X3) significantly affects the Employee Performance Office of Education and Culture of the Province of Papua. Simultaneous and motivation factor (X1), Cultural Organization (X2), and Employee Commitment (X3) significantly affects the Employee Performance Office of Education and Culture of the Province of Papua. The most dominant variable influence on Employee Performance Office of Education and Culture of the province among the three variables above is the motivation factor.